Bovine Interferon-Tau Activates Type I interferon-Associated Janus-signal Transducer in HPV16-positive Tumor Cell - Fierros-Zárate, Geny (J Cancer, 2020)
The mechanisms of signal transduction by interferon-tau (IFN-τ) are widely known during the gestation of ruminants. In trophoblast cells, IFN-τ involves the activation of the JAK-STAT pathway, and it can have effects on other cell types, such as tumor cells. Here we report that the HPV16-positive BMK-16/myc cell treated with ovine IFN-τ, results in the activation of the canonical JAK-STAT and non-canonical JAK-STAT pathway. The MAPK signaling pathway was activated, we detected the proteins MEK1, MEK2, Raf1, STAT3, STA4, STAT5 and STAT6. Moreover, IFN-τ induced the expression of MHC Class I, MX and IP10 in the tumor cells and this response may be associated with the viral replication and with the anti-proliferative and the immunoregulatory effects of IFN-τ.